Varietal and yield of soybean in Madhya Pradesh - Sharma, Purushottam; Dupare, B U (Indian Farming, 2018)
Mapping of the districts according the yield level and soybean area concentration indicated that districts like Rajgarh, Sagar, Shajapur, Shivpuri, Raisen, Vidisha, Khandwa and Hosangabad had high soybean area concentration but marred with low to very low yield level. Efforts towards enhancing yield level in these districts should be the priority of the policy makers. Another set of districts with high yield level and low area under soybean are Narsingpur, Damoh, Bhopal, Balaghat, Gwalior, Jabalpur, Morena and Sheopur. In these districts area expansion under soybean should be targeted coupled with marketing support.